The Role Of Teachers In Developing Social Skills In Children Aged 5-6 Years Through The Field Trip Method - Rosyida , Alfi; Pratama, Lia Ricka (UNIB Press, 2025)
The social abilities of early childhood children develop through direct interaction with environments rich in real experiences. The field trip method provides opportunities for children to learn outside the classroom through visits to educational and recreational sites, thereby promoting meaningful learning. This study aims to describe the strategic role of teachers in stimulating the development of social abilities in children aged 5-6 years through the implementation of field trip methods at RA Jauharotul Mualimin. A qualitative approach with descriptive design was employed in this study, with one teacher serving as the primary informant. Data collection was conducted through structured observation, in-depth interviews, and documentation. Data analysis encompasses reduction processes, visual presentation, and inductive conclusion drawing. The findings indicate that teachers fulfill roles as guides, instructors, motivators, facilitators, and evaluators. During field trip activities, teachers implemented a series of stages, including the preparation of tools and materials, grouping children based on supervisors, prayer recitation, and directing observation toward study objects. These findings confirm the importance of active teacher involvement in supporting children's social development through experience-based learning approaches.